External vascular compression by hyaluronic acid injection via pneumatic microjet device - Alexandra Brugnera Nunes de Mattos; Gabriela Martins Fim; Gabriela Quadri Bortoli; Caroline Erthal; Márcio Guedes Brandão (Sociedade Brasileira de Dermatologia (SBD), 2022)
Filling with hyaluronic acid using a pen that injects with vacuum pressure in the lips region became popular due to not using needles, but it presents risks like any minimally invasive procedure. We present a case of injection of hyaluronic acid with this device in the labial region, which resulted in a subocclusion of the inferior labial artery. It is known that the use of pressure can offer a lower precision than the methods already used classically. Therefore, it is important to warn about the risks of this device, which despite not using needles, presents the same risks of complications.